2016
DOI: 10.1115/1.4032675
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Corner Stall Separation With Plasma Actuators in a Compressor Cascade

Abstract: This paper presents a numerical and experimental assessment of a plasma actuation concept for controlling corner stall separation in a highly loaded compressor cascade. CFD simulations were first carried out to assess actuator effectiveness and determine the best actuation parameters. Subsequently, experiments were performed to demonstrate the concept and confirmed the CFD tool validity at a Reynolds number of 1.5 × 105. Finally, the validated CFD tool was used to simulate the concept at higher velocities, bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…This finding is in accordance with the results of Akcayoz et al [22], which point out that, compared with the endwall plasma actuation, the plasma actuation on the blade suction surface contributes the most to the improvement in the total pressure loss of the compressor cascade. However, this paper finds that, through suppressing the development of the PV, the endwall plasma actuation is more efficient in reducing the flow blockage and improving the static pressure rise of the high-speed compressor cascade.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is in accordance with the results of Akcayoz et al [22], which point out that, compared with the endwall plasma actuation, the plasma actuation on the blade suction surface contributes the most to the improvement in the total pressure loss of the compressor cascade. However, this paper finds that, through suppressing the development of the PV, the endwall plasma actuation is more efficient in reducing the flow blockage and improving the static pressure rise of the high-speed compressor cascade.…”
Section: Discussionsupporting
confidence: 83%
“…Based on their findings, they concluded that increasing the actuation voltage can enhance the control effect of plasma actuation, but, from an energetic point of view, the plasma actuation with lower voltage is more efficient [21]. In 2016, Akcayoz et al [22] published their studies on the plasma control of the compressor corner separation. They evaluated the effects of plasma actuations placed on the blade suction surface and the endwall respectively by suppressing the corner separation in a low-speed highly loaded compressor cascade with both numerical and experimental methods and found that the plasma actuators mounted upstream of the separation on both the suction surface and the endwall were most effective in suppressing the corner separation, while most of the improvement in total pressure loss stemmed from the suction surface actuator.…”
Section: Introductionmentioning
confidence: 99%
“…Notice that the k-ω SST Menter model is used in other numerical works dealing with turbomachinery cascades. Akcayoz et al [14] used the same solver and the same modeling to perform RANS computations on a compressor cascade equipped with plasma actuators, employed to control corner stall separations. Keerthi et al [2] used Ansys CFX R to carry out fully turbulent RANS computations closed with the k-ω SST Menter model on a linear cascade featuring blades oscillating in pitch.…”
Section: Ss Actuatormentioning
confidence: 99%
“…Consistently with the assessments of Ref. [14] and with the experiments of Ref. [38], a force per unit span of 300 mN/m is used in this work.…”
Section: Plasma Modelingmentioning
confidence: 99%
See 1 more Smart Citation